一种不对称结构的交流发电机组并联运行功率分配方法 (2019)
本发明提供了一种不对称结构的交流发电机组并联运行功率分配方法，每台交流发电机组配备功率分配控制器；功率分配控制器将所有交流发电机组识别为主机和从机；主机的功率分配控制器控制主机在额定频率和额定电压下运行；从机的功率分配控制器控制从机在有功功率分配调整目标值和无功功率分配调整目标值下运行。该分配方法保证负载端电压、频率能始终保持额定，而不会因为负载功率的变化而变化；同时保证各台交流发电机组承担的有功功率、无功功率能按照适当比例进行分配，而不会出现较大的差异。 The invention provides a parallel operation power distribution method of AC power generator sets with unsymmetrical structures. Each AC power generator is provided with a power distribution controller. The power distribution controller identifies all AC power generate sets as master machines and slave machines. The power distribution controller of the master machine makes the master machine operate in a rated frequency and rated voltage. The power distribution controller of the slave machine makes the slave machine operate in an active power distribution adjustment target value and a reactivepower distribution adjustment target value. The parallel operation power distribution method has advantages of ensuring rated voltage and frequency at the load end, realizing no change caused by